2019
DOI: 10.1136/bmjopen-2018-025547
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs of Spanish families regarding their family members aged 75 years and over who live alone: a qualitative study

Abstract: ObjectiveThis study aimed to assess the attitudes and beliefs of Spanish families regarding their elderly family members aged 75 years and over who live alone, with consideration of gender and educational differences among the family members.MethodsThis qualitative study was based on the critical social paradigm, the theory of constructivist structuralism and Bourdieu’s theory of sociology of action. Four discussion groups were created with the following distribution of family members based on their gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…the art of nursing practice) to meet the patient's needs. Positive nurse-patient relationships are a foundational component of therapeutic care serving to support informed decision making and subsequent high-quality health outcomes (Molina-Mula et al, 2019).…”
Section: Driversmentioning
confidence: 99%
See 2 more Smart Citations
“…the art of nursing practice) to meet the patient's needs. Positive nurse-patient relationships are a foundational component of therapeutic care serving to support informed decision making and subsequent high-quality health outcomes (Molina-Mula et al, 2019).…”
Section: Driversmentioning
confidence: 99%
“…This evidence is consistent with previous theory literature on relationship building and caring such as Theory of Nursing as Caring (Boykin & Schoenhofer, 1993), Theory of Cultural Care (Leininger, 1988), and Theory of Human Caring (Watson, 2012). While many researchers have explored the impact of the nurse-patient relationship on patient and nurses’ outcomes (Davison & Cooke, 2015; Fahlberg et al, 2016; Molina-Mula et al, 2019) none have attempted to evaluate the impact of holistic gender affirming nursing care.…”
Section: Background and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Social life contributes to the exercise of citizenship, the valorization and insertion of the elderly in the social environment as safe and appropriate environments for the elderly. 3,66 Studies carried out in Brazil have shown that factors such as advanced age over 80 years, visual impairment, low cognitive status, slow gait, and not having family life are associated with a greater chance of non-active aging and social disengagement. Difficulties in evaluating active aging were also presented with several countries researching the subject, but so far, despite the use of instruments already validated with other variables centered on quality of life, not all determinants of active aging proposed by the World Health Organization (WHO) have been postulated.…”
Section: -6mentioning
confidence: 99%